Utilization of dried butterfly pea flower (Clitoria ternatea L.) as a source of natural antioxidants: determination of total flavonoid content and activity test with dpph method - Evan, Yulius Evan Christian; Setiawansyah, Arif (Universitas Mataram, 2025)
Butterfly pea flower (Clitoria ternatea L.) is a herbaceous plant known for its high content of bioactive compounds, particularly flavonoids, which serve as natural antioxidants. Commonly used in traditional medicine and functional foods, this flower's ability to neutralize free radicals makes it a valuable natural resource. This study evaluates the antioxidant potential of dried butterfly pea flowers by determining their total flavonoid content and assessing antioxidant activity using the DPPH method. A key novelty of this research lies in the use of controlled oven drying at 50Â°C, which differs from previous studies employing sunlight drying. This method preserved flavonoids more effectively, resulting in a higher flavonoid content (40.60 mg/100 mg extract) compared to prior reports. Phytochemical screening also detected the presence of saponins and tannins, broadening the understanding of its bioactive profile. Antioxidant activity was evaluated using the DPPH method, yielding an IC50 value of 36.06 ppm, indicating very strong activity. Comparatively, vitamin C as a positive control showed an IC50 value of 2.13 ppm. These findings underscore the advantages of optimized drying and extraction methods, highlighting dried butterfly pea flowers as a promising source of natural antioxidants for applications in functional foods and health products.